Translating African Literature, between orality and writing: the novel "Les soleils des independances", of Ahmadou Kourouma - Akrobou, Ezechiel (Estudios de Traducción, 2012)
The general context of romantic statement of Kourouma Ahmadou, following the example of the French-speaking writers in the South of Sahara, takes into account, the geographical, socio-ethnological, sociolinguistic and socio-historic contexts were bound (connected) to the zone of literary production. These various contextual aspects participate in the preparation (clothing business) of the romantic structure at the writers while contributing to the originality of their literary creation. The specificity of the narrative speech of the French-speaking writer transforms the interest of the translation into major stakes in a process of transposition. The problem which settles (arises) to every translator in front of a literary text likes a certain dependence with regard to the context of the literary speech.